2020
DOI: 10.3390/ijms21155515
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase 2 Deficiency Exacerbates Imiquimod-Induced Psoriasis-Like Skin Inflammation

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) is an enzyme known to suppress immune responses, and several reports have showed that it is associated with psoriasis. IDO2 is an isoform of IDO1, recently identified as a catalytic enzyme in the tryptophan-kynurenine pathway, which is expressed in dendritic cells and monocytes. The expression of IDO2 in immune cells suggests that IDO2 may contribute to immune functions. However, the role of IDO2 in the pathogenesis of psoriasis remains unclear. In this study, to elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…Histological changes in skin lesions showed that the Ki67-positive cells representing epidermal keratinocyte proliferation are mainly found at the dermal junction in IMQ-induced psoriatic skin lesions as reported previously [ 36 , 37 ]. Moreover, the ki16425 treatment significantly reduced epidermal thickening due to IMQ-induced keratinocyte hyperproliferation ( Figure 2 ), suggesting that LPAR1/3 inhibition might decrease keratinocyte proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…Histological changes in skin lesions showed that the Ki67-positive cells representing epidermal keratinocyte proliferation are mainly found at the dermal junction in IMQ-induced psoriatic skin lesions as reported previously [ 36 , 37 ]. Moreover, the ki16425 treatment significantly reduced epidermal thickening due to IMQ-induced keratinocyte hyperproliferation ( Figure 2 ), suggesting that LPAR1/3 inhibition might decrease keratinocyte proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…There have not been fully studied about IDO2 and TDO in psoriasis. IDO2 decreases IL-17 expression, resulting in the suppression of skin inflammation in imiquimod-induced psoriasis-like dermatitis [27]. In the present study, the TRP levels decreased in the PSOs, suggesting IDO1 activation.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast with these studies, in a model of psoriasis-like inflammation, the manifestations of the disease were significantly worse in the IDO2 KO mice (22). In fact, full active IDO2 was endowed with the ability to control the production of proinflammatory IL-17, thus contributing to the suppression of skin inflammation.…”
Section: The "Mystery" Of Ido2 Function: Hints From Autoimmune/chronic Inflammatory Diseasesmentioning
confidence: 64%
“…The fact that IDO2 biology is still far from being understood also derives from the observations that this molecule appears to play opposite functions in both autoimmune and neoplastic diseases. In fact, in mouse experimental models of autoimmunity/chronic inflammation, IDO2 is pathogenetic in arthritis (20,43) and protective in psoriasis (22). In humans, the presence of an IDO2-deficient functional status exerts protective effects in PDAC (29) but increases the risk of developing NSCLC (this study).…”
Section: Discussionmentioning
confidence: 80%